2022
DOI: 10.1182/bloodadvances.2021005978
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of relapsed B-cell acute lymphoblastic leukemia after sequential treatment with blinatumomab and inotuzumab

Abstract: Novel monoclonal antibody-based therapies (mAbs) targeting CD19 and CD22, i.e. blinatumomab and inotuzumab, have demonstrated high rates of complete remission (CR) and been used as a bridging treatment to potentially curative allogeneic hematopoietic stem cell transplantation (alloHCT) in adults with relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia (B-ALL). However, limited data exist on the outcome of patients resistant to both mAbs as well as responses to each agent when progressed after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The absence of problematic GvHD despite moderate DLI doses is also unusual, as many cases reported high rates of severe GvHD using a chemo‐DLI approach [ 3 , 11 ]. Lastly, our timeline was tight, choosing a 15‐day InO‐Blina interval (compared to, e.g., 99 days [ 8 ]). Likewise, DLI applications mostly took place in Blina‐Cycle 3, while we applied them in Cycle 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of problematic GvHD despite moderate DLI doses is also unusual, as many cases reported high rates of severe GvHD using a chemo‐DLI approach [ 3 , 11 ]. Lastly, our timeline was tight, choosing a 15‐day InO‐Blina interval (compared to, e.g., 99 days [ 8 ]). Likewise, DLI applications mostly took place in Blina‐Cycle 3, while we applied them in Cycle 1.…”
Section: Discussionmentioning
confidence: 99%
“…Using Blina/Ino in sequence has not yet been investigated in prospective, randomized trials. But case series show a benefit of the combination [ 8 , 9 ]. Adding low‐intensity chemotherapy was successful in avoiding full‐dose antibody therapy and accompanying side effects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported successful treatment of extramedullary relapse in Philadelphia chromosome positive B-ALL with CD19 + CAR-T although follow up is only available for 8 months 23 . Sequential treatment with inotuzumab and blinatumumab has also been studied 24 . Majority of the larger studies were conducted for patients with bone marrow relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they can be a treatment option for patients who no longer respond to drugs targeting those antigens. Indeed, in one trial, patients relapsed or refractory to blinatumomab who were then treated with the CD22 ADC inotuzumab experienced 68% complete response as a bridge therapy to hemopoietic stem cell treatment (HSCT) [ 25 ]. Additionally, CD22-targeted CAR-T therapies have demonstrated sustained complete responses in patients previously treated with blina or CD19 CAR-T [ 26 ].…”
Section: Introductionmentioning
confidence: 99%